2003
DOI: 10.3349/ymj.2003.44.5.875
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Cigarette Smoking Among Korean American Men

Abstract: This study examined the prevalence and correlated factors of cigarette smoking in a cross-sectional, epidemiological survey of Korean American men living in Maryland (n=333). In this sample, 26.1% were current smokers and 42.3% were former smokers. The older age group (> or = 40 years) was more likely to have quit smoking than the younger age group (< 40 years). In multiple logistic regression analysis, acculturation was associated with smoking status; those who stayed more than 20 years in the U.S. were less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…Each study's purpose was clearly defined in the meta-analysis. Six studies 8,16,17,19,27,28 recruited samples using a simple random sampling frame based on a list of Asian surnames in a telephone directory or random digit dialing, whereas 2 studies 12,29 used a stratified cluster sampling from schools or Asian community organizations. One study 15 used a convenience sampling method in clinical settings.…”
Section: Descriptive Data From Studies In Meta-analysismentioning
confidence: 99%
“…Each study's purpose was clearly defined in the meta-analysis. Six studies 8,16,17,19,27,28 recruited samples using a simple random sampling frame based on a list of Asian surnames in a telephone directory or random digit dialing, whereas 2 studies 12,29 used a stratified cluster sampling from schools or Asian community organizations. One study 15 used a convenience sampling method in clinical settings.…”
Section: Descriptive Data From Studies In Meta-analysismentioning
confidence: 99%
“…With regards to acculturation and smoking prevalence, studies have shown that levels of acculturation were associated with smoking prevalence among Korean Americans (Hofstetter et al, 2004;Juon, Kim, Han, Ryu, & Han, 2003). The more Korean American men were acculturated, the higher the likelihood for Korean American males to quit smoking.…”
Section: Manifestations Of Stress In Korean Americans: Nicotine and Amentioning
confidence: 99%
“…Estimates of smoking prevalence for Korean American men ranged from 26% to 39%, whereas the prevalence rates for Korean American women were low at 3.8% to 8.5% (California Health Interview Survey, 2005;Hofstetter et al, 2004;Juon et al, 2003;Kim et al, 2000;Lee, Sobal, & Frongillo, 2000;Lew et al, 2001). Of note, according to the Korean National Health Ministry survey in 2006, the prevalence of cigarette smoking for men was 50% and for women, 3% (Gallup Korea, 2006).…”
Section: Women (Centers For Disease Control and Preventionmentioning
confidence: 99%